Taxonomy of golf putting: Do different golf putting techniques exist? - McLaughlin, P.; Best, R. (Journal of Sports Sciences, 2013)
This study is a preliminary investigation into the use of cluster analysis to determine if different putting techniques existed in a group of club level golfers.